2018
DOI: 10.1108/ijlls-04-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study: an exploration of its translation beyond Japan

Abstract: Purpose The purpose of this paper is to explore the popularity of Japanese lesson study (JLS) beyond Japan and the challenges this translation might pose. It notes that there is not a universally accepted definition of lesson study (LS) and seeks to identify the “critical components” of JLS through a review of the literature. It then uses a systematic literature review of recent studies of the implementation of LS with in-service teachers beyond Japan to analyse the models of LS used against these seven critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 11 publications
3
83
0
4
Order By: Relevance
“…This may be because teachers and researchers outside of Japan have difficulty understanding the Japanese perspective of lifelong learning goals, where it can take six months to formulate an LS lesson, even when the teachers involved work on it daily (Fujii, 2014). Accordingly, Seleznyov (2018) emphasized that although LS has been frequently used in Western countries, there are remaining challenges in finding a transnational shared understanding of its original core components and in particular how to apply research in practice. In this context, Norwich et al (2020) suggested the need for research measuring the changes and limitations in LS to increase participation, belonging and achievement at the highest possible level in SEND teaching.…”
Section: Prior Researchmentioning
confidence: 99%
“…This may be because teachers and researchers outside of Japan have difficulty understanding the Japanese perspective of lifelong learning goals, where it can take six months to formulate an LS lesson, even when the teachers involved work on it daily (Fujii, 2014). Accordingly, Seleznyov (2018) emphasized that although LS has been frequently used in Western countries, there are remaining challenges in finding a transnational shared understanding of its original core components and in particular how to apply research in practice. In this context, Norwich et al (2020) suggested the need for research measuring the changes and limitations in LS to increase participation, belonging and achievement at the highest possible level in SEND teaching.…”
Section: Prior Researchmentioning
confidence: 99%
“…In its transformation into other countries and schools, it is found that there is much variation in practice. Seleznyov's (2018) In summary, studies of the translation of JLS into contexts beyond Japan show that there is not an internationally shared understanding of JLS. It is interesting to note that several of the often-missing components are those that distinguish JLS as a research process, instead of merely a collaborative approach to professional development.…”
Section: Lesson Study As An Activitymentioning
confidence: 99%
“…Initially, the criticism lesson became a part of lesson study as well as the approach of local normal schools for teacher education while, later on, it found its way from preservice teacher education to in-service professional development. Stigler and Hiebert (1999) are credited with the initial publications about lesson study (modeled in the Japanese tradition) as a method to improve teaching in the North American IJLLS 9,4 context (Seleznyov, 2018). Lesson study, in this context, generally involves groups of teachers or instructors interested in collaborating to develop a "research lesson".…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of planning, doing, checking and acting (see Figure 1) is completed once again with the new lesson (Cerbin and Kopp, 2006). However, other researchers suggested that reteaching a lesson intended for a specific class at a specific point in time is unethical and not considered a component of Japanese lesson study (Seleznyov, 2018). As a middle ground, Seleznyov (2018) recommended that information learned through past research lessons be incorporated into future research lessons.…”
Section: Lesson Study Phasesmentioning
confidence: 99%
See 1 more Smart Citation